Millennium Development Goals, Sustainable Development Goals and the Nigerian Constitution: Veritable Tools for Overcoming Nigeria’s Health Challenges? - Olatoke, Joshua Olukayode (NIU Journal of Social Sciences, 2017)
Health is and has always been pivotal to any meaningful development a nation can achieve. The policies and responsiveness of the government of any state as regards the health of its citizens is a major index for determining the seriousness of the government as regards development. Due to the towering influence of the Millennium Development Goals (MDGs, an off shoot of the 8 th September, 2000 Millennium Declaration) -now replaced with the Sustainable Development Goals (SDGs) on the health sector in Nigeria, any discuss which attempts an appraisal or as little as a highlight of the Government’s response to health in Nigeria, must needs examine the health related goals of the Millennium Development Goals (MDGs) and Sustainable Development Goals (SDGs). Nigeria has no doubt been thoroughly influenced by same in her health policies and in the provision of medical facilities, rural and urban areas inclusive. This work examines the health related goals of the Millennium Development Goals (MDGs) and draws inferences from available data and statistics. It further considers the Millennium Development Goals (MDGs) and the Sustainable Development Goals (SDGs) against the backdrop of the Nigerian Constitutional provisions for health, and puts forward a poser- Whether the Millennium Development Goals (MDGs) cum Sustainable Development Goals (SDGs) are necessary in the first place for overcoming Nigeria’s health challenges in view of the profound Nigerian Constitutional provisions on health? After taking a position, the writer attempts to make a case for the Millennium Development Goals (MDGs) cum Sustainable Development Goals (SDGs), but dismantles all the arguments made in support of the Millennium Development Goals (MDGs) cum Sustainable Development Goals (MDGs), baring its unnecessariness. Finally, this writer proffers recommendations which suggest the way forward so as to ensure that Nigeria’s health aspirations are achieved.